171Yb+ 5D3/2 hyperfine state detection and F = 2 lifetime. (11th March 2015) - Schacht, M; Danielson, J R; Rahaman, S; Torgerson, J R; Zhang, J; Schauer, M M
Abstract: We report on measurements of the lifetime of the state in single ions confined in a radiofrequency quadrupole trap. Experimental parameters that affect hyperfine state preparation and detection efficiency are characterized and optimized. A set of wait times for optimal sampling of the lifetime is chosen and used to measure that lifetime with high statistical sensitivity. A systematic variation in this lifetime seems to be apparent. The source of the variation was not identified, but ion number and cooling rate appear to be ruled out. A net determination is made of ms which is significantly longer than other measurements of the same quantity with four times better statistical precision than the most recent measurement. An alternate shelving scheme is proposed that would provide S – D state discrimination for Yb + even isotopes as well as improved sensitivity for D state hyperfine discrimination in odd isotopes.